Melihat Hubungan Indikator Makro Ekonomi di Indonesia: Inflasi, Pengangguran, dan Pertumbuhan Ekonomi? - Dadang Wibowo; M.Firmansyah (Akuntansi Pajak dan Kebijakan Ekonomi Digital, 2025)
Macroeconomic indicators are essential instruments in the process of planning a country's development. Assumptions regarding inflation, unemployment, and economic growth are often used by governments to determine macroeconomic policies. Given this context, it becomes important to empirically understand the relationship among these three macroeconomic indicators in Indonesia. This study statistically examines the relationship between the variables of inflation, unemployment, and economic growth using the Vector Error Correction Model (VECM) method. The results show that inflation and the open unemployment rate significantly influence economic growth. Inflation has a positive relationship with economic growth, while the open unemployment rate has an inverse relationship with economic growth. In the short term, economic growth is significantly affected by the growth rate in the previous period (lag-1 or t-1). Meanwhile, inflation and the open unemployment rate do not statistically have a significant impact on economic growth. Shocks to inflation and the open unemployment rate are relatively not excessively responded to by economic growth.